Evaluation of Peritumoral Fibrosis in Metastatic Colorectal Adenocarcinoma to the Liver Using Digital Image Analysis. Issue 2 (18th October 2018) - Waters, Kevin M; Cottrell, Tricia R; Besharati, Sepideh; Zhu, Qingfeng; Anders, Robert A
Abstract: Objectives: It is challenging to separate peritumoral fibrosis from fibrosis due to chronic liver disease in mass-directed liver biopsies. We evaluated the distance that peritumoral fibrosis extends from metastatic colorectal adenocarcinoma in liver. Methods: Peritumoral and distant uninvolved liver trichrome stains from 25 cases were analyzed using digital image analysis. Fibrosis was quantitated at concentric intervals from each tumor and in uninvolved liver. Results: There was a 3.9 fold (range 0.9-18.6) median increase in fibrosis in the first 0.5 mm of peritumoral liver compared to distant liver. Fibrosis levels returned to baseline at median 2.5 mm (interquartile range 1.5-5.0 mm) from tumor. Conclusions: Fibrosis is markedly increased in peritumoral liver. Fibrosis levels returned to baseline by 5 mm from tumor in approximately 75% of cases. Pathologists should be cautious of fibrosis in mass-directed liver biopsies without at least 5 mm of liver tissue distal to the mass.